Performance of rat-tail calves - Schalles, R.R.; Powell, Douglas A.; Cundiff, L.V.; Glaze, J.B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The rat-tail syndrome occurs in a small percentage of calves produced by crossing Continental breeds of cattle with Angus or Holstein. These calves are characterized by short, curly, malformed, sometimes sparse body hair and an abnormal tail switch. The performance of 43 rat-tail calves was compared to that of 570 normal calves of the same breeding and contemporary groups. All rat-tail calves were sired by Simmental bulls and were from cows with various percentages of Angus breeding. As the percentage of Angus increased, the frequency of rat-tail calves increased. The rat-tail condition had no effect on birth weight, weaning weight, or gain from birth to weaning. However, the rat-tail calves had significantly lower rates of gain from weaning to yearling (during the winter months) than the normal calves, resulting in 43 lb lighter yearling weights. The gains of steers from yearling to slaughter were not significantly different, but the rat-tail steers were 78 lb lighter (P=.01) and 13 days older (P=.15) at slaughter than the normal steers.
Keywords: Beef; Rat-tail; Cattle; Performance; Genetics